IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (Suatu Studi di Desa Kalasey Dua Kecamatan Mandolang Kabupaten Minahasa) - SLAMET, AYU NINGSI; Ogotan, Martha; Londa, Very (Sam Ratulangi University, 2017)
The village fund allocation of aid programs aim to support the development programs of the village to mensejah terahkan people. Based on Act No. 6 of the year 2014 of the village, the village had a source of income in the form of original income areas, for the results of the local tax and levy County/City, part of the Fund's financial center and the berimbangan received by kabupaten/kota, the allocation of the budget STATE BUDGET, financial assistance from the NATIONAL BUDGETS of the provinces and kabupaten/kota.The focus in this study was the implementation of the policy on allocation of Funds the village to find out the extent of the success of the implementation of the policy of the ADD-ON as seen from the factor endowments and penghambatnya factors. This policy aims to let how ADD can be used with a good, correct and according to needs of the villagers.The research method used is descriptive qualitative approach method. The instruments in this study is the researchers themselves based on indicators of policy implementation theory according to the model of Merilee s. Grindle. Charge indicators will consist of the contents of the policy and the policy context. Data analysis techniques used in this research is interactive analysis techniques according to Miles and Huberman.The results of this research on indicators of policy content (content policy), that ADD it is true – true to the people, although there are still many communities that have a difference of persepdi with the village because of his lack of socialization from the village of Kalasey in the village of ADD to question two, direct benefits perceived by the people of the village also Kalasey two, and then implementing this policy ADD-ON runs pretty most from village chief to the councilor who deal directly with the application of the allocation of funds. Whereas, in the context of the ADD Policy in the village Kalasey, village officials are already running or apply an ADD in accordance with the needs of the community in the village of Kalasey, in addition to Two basic tasks and functions of each of the apparatus of the village though it looks not too good in coordination but until then this is already good enough in communications, both from the village chief, Secretary of the village, the village Treasurer, BPD , and LPM.Keywords: Implementation Of Policy, The Allocation Of Funds.